Evaluasi dan Perbaikan Antarmuka Situs Web Koperasi Karyawan PT. Gudang Garam Tbk. Kediri "MEKAR" Menggunakan Metode Human Centered Design (HCD) - Cantya Danniswara; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Koperasi Karyawan (Kopkar) PT. Gudang Garam Tbk. Kediri "MEKAR" is an official cooperative under the auspices of PT. Gudang Garam Tbk. Kediri and has a website that needs to be improved on its user interface. This is because the website is used as a promotional event and provides information needed by users. The method that will be used to improve the Kopkar website is Human Centered Design (HCD). HCD is an approach to developing interactive systems that take into account or be human centered so that they focus on easy-to-use system design. HCD also has four stages: user context analysis, user and / or stakeholder needs analysis, user interface design, and evaluation of improved websites. The focus of the evaluation carried out in this study was evaluation of usability. At the end of the study, user interface improvements were made and analysis of the results of the comparison of the initial design evaluation and solution design. The results of the comparison of design evaluations obtained were on the initial effectiveness aspects of the design which was 66.4% and the design of the solution increased by 100%. On the aspect of efficiency, the average time needed at the start of the design is 45.406 seconds and the solution design is 4.364 seconds. In the aspect of user satisfaction using the System Usability Scale (SUS) questionnaire, the average value obtained at the beginning of the design was 38.75 while for the solution design the value obtained was 87.91. The evaluation results prove that the designed design has successfully solved the problem.